Emotional prosody in congenital amusia: Impaired and spared processes. (November 2019) - Pralus, A.; Fornoni, L.; Bouet, R.; Gomot, M.; Bhatara, A.; Tillmann, B.; Caclin, A.
Abstract: Congenital amusia is a lifelong deficit of music processing, in particular of pitch processing. Most research investigating this neurodevelopmental disorder has focused on music perception, but pitch also has a critical role for intentional and emotional prosody in speech. Two previous studies investigating amusics' emotional prosody recognition have shown either some deficit or no deficit (compared to controls). However, these previous studies have used only long sentence stimuli, which allow for limited control over acoustic content. Here, we tested amusic individuals for emotional prosody perception in sentences and vowels. For each type of material, participants performed an emotion categorization task, followed by intensity ratings of the recognized emotion. Compared to controls, amusic individuals had similar recognition of emotion in sentences, but poorer performance in vowels, especially when distinguishing sad and neutral stimuli. These lower performances in amusics were linked with difficulties in processing pitch and spectro-temporal parameters of the vowel stimuli. For emotion intensity, neither sentence nor vowel ratings differed between participant groups, suggesting preserved implicit processing of emotional prosody in amusia. These findings can be integrated into previous data showing preserved implicit processing of pitch and emotion in amusia alongside deficits in explicit recognition tasks. They are thus further supporting the hypothesis of impaired conscious analysis of pitch and timbre in this neurodevelopmental disorder. Highlights: Amusics showed preserved emotional prosody recognition in sentences. Amusics showed a deficit for emotional prosody recognition in short voice samples. Preserved intensity ratings of emotions in amusia suggest spared implicit processes.